2015
DOI: 10.3126/ijasbt.v3i3.13287
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chemical Fungicides for the Management of Rice Blast (Pyricularia Grisea) Disease at Jyotinagar, Chitwan, Nepal

Abstract: Rice blast caused by Pyricularia grisea Sacc. is the important disease of rice and different fungicides against this disease were evaluated in summer 2014 at Karma Research and Development Center, Jyotinagar, Chitwan, Nepal. A susceptible rice cultivar ‘Mansuli’ was planted in randomized complete block design and fungicides viz. Tricyclazole  22% + Hexaconazole 3% SC (0.2%), Streptomycin 5% + Thiophanate Methyl 50% WP (0.15%), Prochloraz 25% EC (0.3%), Kasugamycin 2% WP (0.2%), Hexaconazole 4% + Zineb 68 % WP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 7 publications
4
15
0
Order By: Relevance
“…Polyoxins are well-known as inhibitors of cell wall biosynthesis that suppress the formation of germ tubes and appressoria [41, 68–70]. The findings of this research were also comparable to the activities of several commercially available fungicides such as blasticidin-S, kasugamycin, streptomycin and tricyclazole, which demonstrated strong antifungal efficacy against many phytopathogenic fungi, like rice blast fungus M. oryzae Oryzae (MoO) [11, 71–73]. This study for the first time showed that two secondary metabolites of Streptomyces spp.…”
Section: Discussionsupporting
confidence: 60%
“…Polyoxins are well-known as inhibitors of cell wall biosynthesis that suppress the formation of germ tubes and appressoria [41, 68–70]. The findings of this research were also comparable to the activities of several commercially available fungicides such as blasticidin-S, kasugamycin, streptomycin and tricyclazole, which demonstrated strong antifungal efficacy against many phytopathogenic fungi, like rice blast fungus M. oryzae Oryzae (MoO) [11, 71–73]. This study for the first time showed that two secondary metabolites of Streptomyces spp.…”
Section: Discussionsupporting
confidence: 60%
“…Rice blast, caused by Pyricularia oryzae (teleomorph = Magnaporthe oryzae) is one of the most important diseases, due to its worldwide distribution, destructiveness and high degree of pathogenicity (Thuan et al, 2006;Rodríguez et al, 2007). Rice blast can cause up to 100% in yield reduction, depending on the cultivar susceptibility, cropping technology and climatic conditions (Prabhu et al, 2009, Magar et al, 2015. Although infections are mostly reported to occur in leaves and stems, seeds and roots may also be infected by P. oryzae, using the typical developmental processes of root-infecting fungi (Sesma and Osbourn, 2004).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…Although finger millet is considered a hardy crop, it is affected by more than 20 diseases, of which blast disease caused by Pyricularia grisea is the most devastating (Prajapati et al, 2013 ; Waghunde et al, 2013 ; Magar et al, 2015 ; Cruz and Valent, 2017 ). The pathogen infects different parts and stages of the plants from seedling to grain formation, causing diamond-shaped lesions and premature drying of young leaves, affecting the panicle and causing neck and/or finger blast leading to yield loss up to 100% that result in economic loss to farmers and ultimately food crisis (Senthil et al, 2012 ; Prajapati et al, 2013 ; Negi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogen infects different parts and stages of the plants from seedling to grain formation, causing diamond-shaped lesions and premature drying of young leaves, affecting the panicle and causing neck and/or finger blast leading to yield loss up to 100% that result in economic loss to farmers and ultimately food crisis (Senthil et al, 2012 ; Prajapati et al, 2013 ; Negi et al, 2015 ). Control of blast disease is a serious and challenging issue relying heavily on chemical pesticides like organophosphorus fungicides which have been reported to be highly effective (Kumar and Kumar, 2011 ; Magar et al, 2015 ). However, extended use of chemical pesticides has resulted in the development of pesticide-resistant fungal pathogens, with negative effects on the ecosystem, soil fertility, and water quality, leading to serious health problems including birth defects (Hawkins et al, 2014 ; Hollomon, 2016 ).…”
Section: Introductionmentioning
confidence: 99%